Is local best? Examining the evidence for local adaptation in trees and its scale - Boshier, D.; Broadhurst, L.; Cornelius, Jonathan P.; Gallo, L.; Koskela, Jaarko; Loo, J.; Petrokofsky, G.; St Clair, B. (Springer, 2015)
Although the importance of using local provenance planting stock for woodland production, habitat conservation and restoration remains contentious, the concept is easy to understand, attractive and easy to ‘sell’. With limited information about the extent and scale of adaptive variation in native trees, discussion about suitable seed sources often emphasises “local” in a very narrow sense or within political boundaries, rather than being based on sound evidence of the scale over which adaptation occurs. Concerns exist over the actual scale (magnitude and spatial scale) of adaptation in trees and the relative dangers of incorrect seed source or restricted seed collection, leading to the establishment of trees with restricted genetic diversity and limited adaptive potential. Tree provenance and progeny field trials in many parts of the world have shown the existence of genotype by environment interaction in many tree species, but have not necessarily looked at whether this is expressed as a home site advantage (i.e. whether provenance performance is unstable across sites, and there is better performance of a local seed source). This review will examine the evidence for local adaptation and its scale in a number of native tree species from different trial sites across the globe (e.g. tropical, Mediterranean, temperate). These trials have been measured and in some cases results published in a range of formats. The data have, however, usually been presented in the form of which provenances grow best at which sites. The review will examine existing data (published and unpublished) in the context of the scale of local adaptation, with the results being presented in two formats: (a) relating survival, performance of provenances (classified by seed zone/provenance region of origin) to seed zone/provenance region of the planting site; (b) plotting survival, performance provenances against the distance (Euclidean/ecological) between the provenance and the trial site.